2018
DOI: 10.1111/famp.12417
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Relational Preferences Through Transforming Interpersonal Patterns

Abstract: Family therapy has often been conceptualized as a conversational process whereby therapists and clients generate new meanings. Based on a 3‐year study of conversational practices observable in successful family therapy processes of Chilean families with a child/adolescent who is engaged in disruptive behaviors, we looked for clinical examples of Transforming Interpersonal Patterns (TIPs). TIPs are a key aspect of the IPscope, a framework we used to explore the meaning‐making processes in family therapy. TIPs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 27 publications
1
8
0
7
Order By: Relevance
“…For this study, we identified 27 conversational micro-practices, which we called realizers. Assuming a theoretical principle of reflexivity (Gaete et al, 2020; Tomm, 1987), or the notion that a human system engaged in conversationally bringing forth its preferred way of living together may reflexively activate (‘realize’) that very way of living. Through these realizers, participants produce agreements on preferable ways of relating (PR), including ways of doing (behaviours), feeling (emotions) and thinking (values).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…For this study, we identified 27 conversational micro-practices, which we called realizers. Assuming a theoretical principle of reflexivity (Gaete et al, 2020; Tomm, 1987), or the notion that a human system engaged in conversationally bringing forth its preferred way of living together may reflexively activate (‘realize’) that very way of living. Through these realizers, participants produce agreements on preferable ways of relating (PR), including ways of doing (behaviours), feeling (emotions) and thinking (values).…”
Section: Discussionsupporting
confidence: 84%
“…That is, M traces an RP when she witnesses a change (without linguistically or explicitly articulating what the change consists of). The fourth column of Table 3 shows six other tracing realizers, which have been described in another previous report for this same study (Gaete et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the difficulty here may be technical: instead of effectively handling PDB, traditional responders may feel that they only escalate in conflict. Former effective disciplinary methods such as punitive and exclusionary strategies beget only more turmoil and conflict ( Patterson, 1982 ; Baumrind, 1991 ; Borum et al, 2010 ; Omer, 2011 ; Osher et al, 2014 ; Gaete et al, 2020 ; Gaete and Gaete, 2021 ). Whether it is imposing alien preferences coupled with disregarding such views, criticizing coupled with defending, or blaming, accusing, and attacking coupled with counterattacking, such interpersonal patterns of mutually triggering behaviors may arguably acquire life on its own resulting in increasing appearances of PDB (see Tomm et al, 2014 ; Sametband and Strong, 2018 ).…”
Section: Postdisciplinary Resistance To Normalizing Practicesmentioning
confidence: 99%
“…This issue contains several fine examples of research aimed to inform practice and practice that incorporates research and raises research questions. To single out one example, Gaete et al () present a research study extending Tomm's () concept of transforming interpersonal patterns (TIFs). At the heart of this paper is a simple and persuasive idea: There are family experiences that promote problematic interaction patterns and others that lead to more positive family experience.…”
mentioning
confidence: 99%